Attachment in the Early Life Course: Meta‐Analytic Evidence for Its Role in Socioemotional Development. (14th November 2016) - Groh, Ashley M.; Fearon, R. M. Pasco; van IJzendoorn, Marinus H.; Bakermans‐Kranenburg, Marian J.; Roisman, Glenn I.
Abstract: After decades of research on early attachment relationships, questions remain concerning whether the evidence supports claims made by attachment theory, in particular, that variation in early attachment predicts children's developmental adaptation or maladaptation, and that characteristics of children's temperament does not determine attachment. To evaluate these claims, we conducted meta‐analyses on early attachment and children's social competence with peers, externalizing problems, internalizing symptoms, and temperament. In this article, we summarize our findings, which support attachment theory—though we note caveats. We also call for new measurement models, a focus on mediating and moderating mechanisms, and multisite replications.